KORXONALAR FAOLIYATIDA EKOLOGIK INNOVATSIYALARNING IQTISODIY SAMARASI - Xalimov Shoxjaxon Xakimjon o‘g‘li, (TADQIQOTLAR, 2026)
ABSTRACT This  article  analyzes  the  economic  effects  of  implementing  environmental innovations in enterprise activities. The study examines the impact of eco-innovations on production costs, resource efficiency, and financial performance of enterprises. The findings indicate that environmental innovations may require additional investments in the short term; however, in the long run they contribute to cost reduction and economic sustainability.  Moreover,  eco-innovations  enhance  enterprise  competitiveness  and reduce environmental risks. The article substantiates the importance of a gradual and strategic implementation of environmental innovations in business activities.